2019
DOI: 10.3390/toxins11060326
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Toxin Genes in Clinical Isolates of Clostridium perfringens: Coexistence of Alpha-Toxin Variant and Binary Enterotoxin Genes (bec/cpile)

Abstract: Clostridium perfringens (C. perfringens) is responsible for food-borne gastroenteritis and other infectious diseases, and toxins produced by this bacterium play a key role in pathogenesis. Although various toxins have been described for C. perfringens isolates from humans and animals, prevalence of individual toxins among clinical isolates has not yet been well explored. In the present study, a total of 798 C. perfringens clinical isolates were investigated for prevalence of eight toxin genes and their genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…The clinical relevance of these non-typing toxins is supported by a recent study on human strains that proposed a further provisional classification for C. perfringens strains. The toxinotype H1 was created for the presence of the cpa toxins and the minor toxin cpb2, and the toxinotype H2 was designed for the presence of the cpa , cpe, and cpb2 genes [ 50 ]. Regarding the cpb2 gene, the authors could not discriminate between the two variants, but the molecular tools applied in our study could offer the possibility to differentiate between the two cpb2 variants and even further characterize the classification into H1 and H2 cons and aty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical relevance of these non-typing toxins is supported by a recent study on human strains that proposed a further provisional classification for C. perfringens strains. The toxinotype H1 was created for the presence of the cpa toxins and the minor toxin cpb2, and the toxinotype H2 was designed for the presence of the cpa , cpe, and cpb2 genes [ 50 ]. Regarding the cpb2 gene, the authors could not discriminate between the two variants, but the molecular tools applied in our study could offer the possibility to differentiate between the two cpb2 variants and even further characterize the classification into H1 and H2 cons and aty.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of association of the cpe gene with the etx gene in the toxinotype D (12/19) could be explained by the different localization of the cpe locus. In human food poisoning, the cpe gene is localized in a variable region of the chromosome carrying the IS 1470 sequence, while in bacteria isolated from human cases of non-food borne gastrointestinal disease or from infected animals, the cpe gene is localized on plasmids and is flanked by the IS 1470- like sequence or the IS 1151 sequence [ 21 , 50 , 51 ]. The etx gene, encoding the ETX toxin, is also linked to the IS 1151 sequence and this suggests that cpe and etx are located in the same mobile element [ 6 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, several reports have shown that the frequency of type F C. perfringens among healthy humans was 6–31% [ 9 , 10 , 11 , 12 ]. Second, the predominant cpe locus of the isolates from healthy humans and sporadic diarrhea cases in Japan was a plasmid with a IS 1151 sequence [ 37 , 38 ]. Finally, type F C. perfringens was isolated from few human-unrelated samples [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, probably the high detection frequency of type F C. perfringens from healthy humans is partially because of bivalves such as asari clams since our MLST result has shown that the sequences of the isolates from a human and asari clams were linked to each other, but those from retail meats were clearly different. The MLST result of Matsuda et al has shown that some of the isolates from humans were ST41 [ 38 ] by Xiao’s scheme [ 40 ], which is the same as the asari clam clone.…”
Section: Discussionmentioning
confidence: 99%
“…perfringens is a Gram-positive anaerobic rod-shaped bacterium that is categorized into seven types (A-G), according to the production of major toxins, specifically alpha (CPA), beta (CPB), epsilon (ETX) and iota (ITX), plus enterotoxin (CPE) and NetB toxin (NetB) (25). Anaerobic culture was only performed in six out of the ten specimens, all of which were positive for C. perfringens, with A and A β2 -subtypes found in three and two of these five cases respectively, highly suggesting an association between C. perfringens type A infection and the development of NBEI (26). C. perfringens was isolated in heavy growths from Case B9; however, the samples were misplaced before toxinotyping could be performed.…”
Section: Discussionmentioning
confidence: 99%